Energy of Rural Spaces – Technical, Economic and Social Analysis of Renewable Energy in Isolated Communities - Maravela, Gabriela Larisa; Vatuiu, Teodora (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
With the arising necessity of new homes for the population also comes the necessity of energy for heating and electricity. In big cities the energy is easily attainable while the most remote areas have difficulties finding reliable sources of energy. In Romania, home heating in remote villages is usually provided through wood burning, using a fireplace or a boiler. The access to the electricity is assured only to the villages in proximity of the cities, main reason being the enormous price for the connection of few households to the national power grid, which makes the electricity directly related to poverty. Access to electricity may improve economic and social status of isolated communities. One of the main advantages of renewable energy, is its decentralized characteristic. This means that every household can produce its own energy without relying on the national power grid. This paper aims to research, from a techno-economic point of view, the possibility of creating small power grids in remote villages from Dobrogea - Romania and its social benefits for the communities. The first step is to identify how many villages in Dobrogea do not have access to electricity, to analyze from a technical, economic, social and environmental perspective the possibility of implementing project in rural areas by using mathematical models. Second step is to identify possibilities of private or governmental funding for implementing such projects.